REPRESENTASI TRADISI UPA-UPA (MANGUPA) SEBAGAI SIMBOL DALAM PENDIDIKAN KRISTIANI PADA MASYARAKAT BATAK - Panggabean, Justice Zeni Zari (Moriah Theological Seminary, 2025)
The Mangupa-upa tradition is one of the cultural practices rooted in the value system of the Batak people, which has undergone a process of adaptation and transformation along with the entry of Christianity into the Batak Land. This study aims to examine how Mangupa-upa is not only maintained as a cultural heritage, but also reinterpreted as an expression of Christian faith in the context of modern Batak. Using library research methods and a phenomenological approach, this study analyses the symbolic meaning of Mangupa-upa and its transformation in the spiritual and social life of the Christian Batak community. The results show that symbolic elements in this tradition such as giving blessings, prayers, and wearing ulos have received theological reinterpretation as symbols of God's blessings, sending, and inheritance of faith. This transformation reflects the creative dynamics of inculturation between Christian faith and local culture. Furthermore, this study recommends the integration of Mangupa-upa values into the Christian religious education curriculum contextually as a means of relevant faith education rooted in cultural identity. Thus, Mangupa-upa is not only a symbol of tradition, but also a medium for spreading the Gospel which affirms noble values such as solidarity, gratitude, and prayer in the light of the Christian faith. Tradisi Mangupa-upa merupakan salah satu praktik budaya yang berakar dalam sistem nilai masyarakat Batak, yang telah mengalami proses adaptasi dan transformasi seiring masuknya Kekristenan ke Tanah Batak. Penelitian ini bertujuan untuk mengkaji tradisi Mangupa-upa tidak hanya dipertahankan sebagai warisan budaya, tetapi juga dimaknai ulang sebagai ekspresi iman Kristen dalam konteks Batak modern. Dengan menggunakan metode penelitian pustaka dan pendekatan fenomenologis, kajian ini menganalisis makna simbolik dari Mangupa-upa dan transformasinya dalam kehidupan spiritual dan sosial masyarakat Batak Kristen. Hasil analisis menunjukkan bahwa unsur-unsur simbolik dalam tradisi ini seperti pemberian berkat, doa, dan pemakaian ulos telah memperoleh reinterpretasi teologis sebagai lambang berkat Allah, pengutusan, serta pewarisan iman. Transformasi ini mencerminkan dinamika kreatif inkulturasi antara iman Kristen dan budaya lokal. Lebih lanjut, penelitian ini merekomendasikan integrasi nilai-nilai Mangupa-upa ke dalam kurikulum pendidikan agama Kristen secara kontekstual sebagai sarana pendidikan iman yang relevan dan berakar pada identitas budaya. Dengan demikian, Mangupa-upa tidak hanya menjadi simbol tradisi, tetapi juga media pewartaan Injil yang mengafirmasi nilai-nilai luhur seperti solidaritas, syukur, dan doa dalam terang iman Kristen.